REFERENCES VALUES OF DRIS FOR SOYBEAN, cv.CD 202, IN THE SOUTH OF THE MATO GROSSO DO SUL STATE, BRAZIL - MAEDA, Shizuo; RONZELLI Júnior, Pedro; LUCCHESI, Luiz Antônio Correa (Scientia Agraria, 2004)
In cerrado region of Mato Grosso do Sul state, Brazil, the intensive application of calcareous and fertilizer was necessary to soybean productions. Soil and leaf analysis have been the mostly used criteria for soil fertility management and nutritional status characterization. For that purpose, analytical results of soil and leaves sample was interpreted by means concentrations ranges criteria. However, it is well known that the resultant interpretation done in an isolated way for each nutrient by the critical concentration ranges criteria are difficult to be organized under a hierarchy of limitations and are affected by several factors such as variety, tissue age, climate and soil properties, points which constitute restrictions for the validity and quality of recommendations based on them. In order to overcome such limitations some authors have proposed an alternative interpretation method, the Diagnosis and Recommendation Integrated System (DRIS), considered less susceptible but yet influenced by some factors in its discriminatory ability and efficiency of diagnosing plant nutrition status, and thus requiring the development of reference values for its regional application. The aim of this work was to develop and to valid reference values for soybean crops cultivated in Mato Grosso do Sul state. For that purpose leaves and soybean grain were sampled in commercial areas, always from same sites. Regional reference values based on the leaf samples were validated by comparing DRIS interpretation with the visual diagnosis method. The efficacy and the ability to discriminate and to order nutritional problems were better for DRIS than for the other tested methods. This was demonstrated when data from a leaf sample presenting a classical Mn visual deficiency symptom led DRIS to rank Mn as the most limiting nutrient. On the other hand, the difference between outputs given by DRIS based on published values and DRIS based on regional values suggests that refinement of reference values may be beneficial when an improvement in DRIS accuracy is required.